Genealogy and Implementation of Green Finance in Asia and Indonesia - Gea, Marinus; Sadalia, Isfenti; Absah, Yeni (KnE Social Sciences, 2024)
Green finance continues to be developed in the ways with the international community’s agreed-realized sustainable development program. Therefore, through this article, we aim to trace genealogy and implementation of green finance in Asia, especially Indonesia, focused on: (a) providing a conceptual and practical explanation of green finance in Asia and Indonesia; (b) describing mechanisms and challenges faced by Asia and Indonesia in implementing green finance programs; and (c) examining strategic policies in Asia and Indonesia to enhance the involvement of institutional investors and private investments in green projects. The research method used in this study is library research. Through library research, relevant references were searched, studied, analyzed, and reflected upon as research findings. The literature sources include textbooks, journals, and other sources related to green finance. The research findings indicate that: (a) The signing of the Paris Agreement in 2015 impacted 196 countries legally bound and committed to including green development as a strategic policy of their respective countries; (b) The lack of clear mechanisms to realize green finance programs is a major challenge for countries in Asia and Indonesia; (c) To date, there are still few countries with binding policies for involving investors in green projects. Keywords: sustainable development, green finance, green investment